Functional Microdomains in Heart’s Pacemaker: A Step Beyond Classical Electrophysiology and Remodeling - Lang, Di; Glukhov, Alexey V. (Frontiers in Physiology, 2018)
Spontaneous beating of the sinoatrial node (SAN), the primary pacemaker of the heart, is initiated, sustained, and regulated by a complex system that integrates ion channels and transporters on the cell membrane surface (often referred to as “membrane clock”) with subcellular calcium handling machinery (by parity of reasoning referred to as an intracellular “Ca2+ clock”). Stable, rhythmic beating of the SAN is ensured by a rigorous synchronization between these two clocks highlighted in the coupled-clock system concept of SAN timekeeping. The emerging results demonstrate that such synchronization of the complex pacemaking machinery at the cellular level depends on tightly regulated spatiotemporal signals which are restricted to precise sub-cellular microdomains and associated with discrete clusters of different ion channels, transporters, and regulatory receptors. It has recently become evident that within the microdomains, various proteins form an interacting network and work together as a part of a macromolecular signaling complex. These protein–protein interactions are tightly controlled and regulated by a variety of neurohormonal signaling pathways and the diversity of cellular responses achieved with a limited pool of second messengers is made possible through the organization of essential signal components in particular microdomains. In this review, we highlight the emerging understanding of the functionality of distinct subcellular microdomains in SAN myocytes and their functional role in the accumulation and neurohormonal regulation of proteins involved in cardiac pacemaking. We also demonstrate how changes in scaffolding proteins may lead to microdomain-targeted remodeling and regulation of pacemaker proteins contributing to SAN dysfunction.